2012
DOI: 10.1016/j.icheatmasstransfer.2012.07.008
|View full text |Cite
|
Sign up to set email alerts
|

Constructal optimisation of conjugate triangular cooling channels with internal heat generation

Abstract: This paper presents the development of the three-dimensional flow architecture of conjugate cooling channels in forced convection with internal heat generation within a solid.Two types of cross-section channel geometries were used. The first involved equilateral triangles with three equal legs in length and all three internal angles of 60 0 . The second was isosceles right triangles with two legs of equal length and internal angles of 90 0 , 45 0 and 45 0 .Both the equilateral triangle and isosceles right tria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…This current research is an extension of past works [38][39][40] on the application of this theory, where it was shown that the minimized peak temperature was influenced by geometric configurations. The present configuration is considered based on our desire to find the effect of variable cross-section on minimized peak temperature.…”
Section: Introductionmentioning
confidence: 52%
“…This current research is an extension of past works [38][39][40] on the application of this theory, where it was shown that the minimized peak temperature was influenced by geometric configurations. The present configuration is considered based on our desire to find the effect of variable cross-section on minimized peak temperature.…”
Section: Introductionmentioning
confidence: 52%
“…Many researchers have showed that it is valid for both animate [21][22][23][24][25][26][27][28][29][30][31] and inanimate [30][31][32][33][34]. Furthermore, Constructal law also plays a significant role in the design optimization of engineering systems (see, for example, [35][36][37][38][39][40][41][42][43][44]). In this work, we address the design of micromixer based on the Constructal law.…”
Section: Introductionmentioning
confidence: 99%